The Effectiveness of Organizational Management in Community Empowerment Programs: A Case Study of the Community Empowerment Institution (LPM) in Rempoa Urban Village - Darul Fahmi; Lukman Anthoni; Rahman Faisal (Abdimas Paspama, 2025)
This community service program aimed to enhance the effectiveness of organizational management within the Community Empowerment Institution (LPM) in managing community development programs in Rempoa Urban Village, Ciputat Timur, South Tangerang. LPM plays a strategic role in improving social and economic welfare through the planning, implementation, and monitoring of empowerment programs. However, challenges such as limited resources, weak coordination, and unsystematic program structures hinder their effectiveness. The program applied participatory methods including assessments, presentations, discussions, and mentoring involving LPM administrators and community members. Results showed improvements in LPM’s managerial capacity, program planning, stakeholder collaboration, and community engagement. In addition, the program contributed to increasing sustainability, economic independence, and professional credibility of LPM. Nevertheless, issues such as low public participation, inadequate monitoring, and the lack of consistent program documentation were identified. Strengthening internal communication, adopting bottom-up approaches, and building strategic partnerships are recommended. The program concludes that continuous support and adaptive management are essential for long-term community empowerment success.